2019
DOI: 10.1002/chem.201903188
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free Fast Azidation by Using Tetrabutylammonium Azide: Effective Synthesis of Alkyl Azides and Well‐Defined Azido‐End Polymethacrylates

Abstract: An effective method to synthesize azido‐end polymethacrylates from tetrabutylammonium azide (BNN3) in a nonpolar solvent (toluene) was developed. Several low‐mass alkyl halides were reacted with BNN3 in toluene as model reactions and the rate constants of these reactions were determined, to confirm fast BNN3 azidation for tertiary and secondary halides. The end‐group transformation of halide‐end polymethacrylates was effective and nearly quantitative. Notably, the combination of organocatalyzed living (or reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…An alternative method, using TBAN3 in a non-polar solvent (toluene) has been developed, allowing nearly quantitative azidation of halide-end polymethacrylates with no large excess of azide (eq 22). 19 PMMA X (24) Schmidt Reaction. The Schmidt reaction, which enables N-insertive synthesis of secondary amides from ketones, typically uses NaN3 under acidic conditions to generate hazardous hydrazoic acid (HN3) in situ.…”
Section: Nucleophilic Azidation Of Alkyl Halides the Synthesis Of Alk...mentioning
confidence: 99%
“…An alternative method, using TBAN3 in a non-polar solvent (toluene) has been developed, allowing nearly quantitative azidation of halide-end polymethacrylates with no large excess of azide (eq 22). 19 PMMA X (24) Schmidt Reaction. The Schmidt reaction, which enables N-insertive synthesis of secondary amides from ketones, typically uses NaN3 under acidic conditions to generate hazardous hydrazoic acid (HN3) in situ.…”
Section: Nucleophilic Azidation Of Alkyl Halides the Synthesis Of Alk...mentioning
confidence: 99%
“…Recently, a variety of new azidation reagents have been developed, such as azido‐trimethylsilane, [12] diphenyl azidophosphate, [13] and Zhdankin reagent, [14] all of which have been demonstrated efficient toward small‐molecule compounds. Unfortunately, only very few studies have been reported on the preparation of azide polymers in a NaN 3 ‐free manner, which, however, either involved even more risky azide‐containing reagents, [15] or still required the usage of large amounts of organic solvents [16] . Meanwhile, since ionic liquids (ILs) have been widely used as green solvents in macromolecular reactions in recent years owing to their nonvolatility, chemical stability, and high solubility, [17] researchers have also explored the possibility of application of ILs in the synthesis of azide polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, only very few studies have been reported on the preparation of azide polymers in a NaN 3free manner, which, however, either involved even more risky azide-containing reagents, [15] or still required the usage of large amounts of organic solvents. [16] Meanwhile, since ionic liquids (ILs) have been widely used as green solvents in macromolecular reactions in recent years owing to their nonvolatility, chemical stability, and high solubility, [17] researchers have also explored the possibility of application of ILs in the synthesis of azide polymers. However, in these cases, ILs were only used as catalysts or co-solvents, and a large excess of NaN 3 and high reaction temperatures were still mandatory.…”
Section: Introductionmentioning
confidence: 99%
“…Tetrabutylammonium azide (BNN 3 ) was also used instead of NaN 3 . 91 Different from NaN 3 , BNN 3 led to the substitution even in non-polar solvents. This feature enabled the post-azidation of fluorinated (super-hydrophobic) polymer-I in nonpolar solvents, which are otherwise insoluble in polar solvents.…”
mentioning
confidence: 98%